The effect of radiation therapy in the treatment of adult soft tissue sarcomas of the extremities: a long‐term community‐based cancer center experience. (11th February 2017) - Kneisl, Jeffrey S.; Ferguson, Chad; Robinson, Myra; Crimaldi, Anthony; Ahrens, Will; Symanowski, James; Bates, Michael; Ersek, Jennifer L.; Livingston, Michael; Patt, Joshua; Kim, Edward S.
Abstract: The aim of the study was to determine the effect of external beam radiotherapy (RT) in the treatment of extremity soft tissue sarcoma (STS) before or after limb‐sparing surgery (LSS) in a community‐based setting. Patients presenting to our institution from 1992 to 2010 and meeting eligibility criteria were stratified into low (G1) or high (G2, G3) pathologic grade and evaluated. Major complication events, including amputation, radiation‐induced sarcoma, and pathologic fracture, were assessed. Kaplan–Meier techniques and Cox proportional hazards regression models were used. One hundred and sixty‐two eligible patients underwent LSS for extremity STS (120 high grade, 42 low grade). Median time of follow‐up was 5.1 years (0.8–20.3 years). RT was administered to 111 patients. In unadjusted models, RT significantly decreased the risk of local recurrence (LR) in high‐grade STS patients ( P = 0.005) and had a trend for improved recurrence‐free survival (RFS) ( P = 0.069). In multivariable‐adjusted models, RT significantly improved time to LR ( P = 0.001), RFS ( P = 0.003), and overall survival (OS) ( P = 0.003). Analysis of all patients showed those who underwent RT had a major complication rate (MCR) of 16.2%, compared to 3.9% in the no RT group ( P = 0.037); however, the difference in MCR did not differ significantly when the analysis was restricted to high‐grade sarcomas. In our large experience of patients with extremity STS undergoing limb sparing surgery (LSS), RT significantly improved local recurrence (LR), RFS, and OS, in patients with high‐grade tumors. Efficacy benefits of RT should be weighed against potential complications. External beam RT should be considered in patients with resected high‐grade sarcomas. Abstract : The purpose of this study was to determine the effect of external beam radiotherapy (RT) in the treatment of extremity soft tissue sarcoma (STS) before or after limb sparing surgery (LSS) in a community‐based setting. Patients presenting to our institution from 1992 to 2010 and meeting eligibility criteria were stratified into low or high pathologic grade, and survival and major complications were assessed. In our large experience of patients with extremity STS undergoing LSS, RT significantly improved local recurrence, recurrence‐free survival, and overall survival, in patients with high‐grade tumors.